A novel bacterial symbiont association in the hispid beetle, Octodonta nipae (Coleoptera: Chrysomelidae), their dynamics and phylogeny. (May 2018) - Ali, Habib; Muhammad, Abrar; Islam, Saif Ul; Islam, Waqar; Hou, Youming
Abstract: The hispid leaf beetle, Octodonta nipae (Maulik), (Coleoptera: Chrysomelidae), is a devastating pest of palm cultivation worldwide. Endosymbiotic bacteria in the genus Wolbachia are arguably one of the most abundant bacterial group associated with arthropods. Owing to its critical effects on host reproduction, Wolbachia has garnered much attention as a prospective future tool for insect pest management. However, their association, infection dynamics, and functionality remain unknown in this insect pest. Here, we diagnosis for the first time, the infection prevalence, and occurrence of Wolbachia in O. nipae . Experimental evidence by the exploration of wsp gene vindicate that O. nipae is naturally infected with bacterial symbiont of genus Wolbachia, showing a complete maternal inheritance with shared a common Wolbachia strain ( w Nip). Moreover, MLST ( gatB, fbpA, coxA, ftsZ, and hcpA ) analysis enabled the detections of new sequence type (ST-484), suggesting a particular genotypic association of O. nipae and Wolbachia . Subsequently, quantitative real-time PCR (qPCR) assay demonstrated variable infection density across different life stages (eggs, larvae, pupae and adult male and female), body parts (head, thorax, abdomen), and tissues (ovaries, testes, and guts). Infection density was higher in egg and female adult stage, as well as abdomen and reproductive tissues as compared to other samples. Interestingly, Wolbachia harbored dominantly in a female than the male adult, while, no significant differences were observed between male and female body parts and tissues. Phylogeny of Wolbachia infection associated with O. nipae rectified from all tested life stages were unique and fall within the same monophyletic supergroup-A of Wolbachia clades. The infection density of symbiont is among the valuable tool to understand their biological influence on hosts, and this latest discovery would facilitate the future investigations to understand the host-symbiont complications and its prospective role as a microbiological agent to reduce pest populations. Highlights: DNA samples were taken from different life-stages, body parts and tissues of O. nipae and infection was confirmed by qPCR. Wolbachia infection was higher in egg and female adult stage, as well as abdomen and reproductive tissues of O. nipae. wsp and MLST genes displayed that O. nipae is naturally infected with bacterial symbiont of genus Wolbachia ( w Nip). MLST analysis detected a new sequence type (ST-484) for the first time in the present study. Wolbachia infection in O. nipae belongs to monophyletic supergroup-A of Wolbachia clades.